HUBUNGAN ANTARA KECERDASAN EMOSIONAL DAN PENYESUAIAN PERNIKAHAN PADA PRIA DEWASA AWAL DI DENPASAR - Putu Yunita Trisna Dewi; Ni Made Ari Wilani (Jurnal Psikologi Udayana, 2016)
Getting married and starting a new family are one of the developing tasks in the early adulthood. In the first 2 years of marriage, couples need to do a marital adjustment. One of the factors that support the successful of marital adjustment is the ability to express feelings to your partner. Men find it difficult to express their feelings for their traditional views about gender roles in society oriented men and Denpasar most people still follow this view. The traditional view emphasizes men as breadwinners, a figure that is strong, not easy to complain and suppress his feelings. The ability to express emotions have a strong relationship with the marital adjustment so that it takes emotional intelligence in the marriage relationship. The aim of this study is to find out the relation between emotional intelligence and marital adjustment among early adulthood men in Denpasar.This study is a quantitative correlation study. The amount of the subject in the study is 66 young adult men with the criteria of the age limit is 20 – 40 years old, have been married with the age of marriage is not more than 2 years. The technique of collecting data used was purposive sampling. The measuring instrument used in the study was emotional intelligence scale with the reliability 0,885 and the scale of marital adjustment with the reliability 0,882. The result after examining the hypotheses by using the method of correlation data analysis by Spearman shows that the significance level is 0,008 (sig<0,05). The value is showing that there is a significant correlation between emotional intelligence and marital adjustment among early adulthood men. The correlation coefficient between emotional intelligence and marital adjustment is 0,323 that means 32,3% variations in marital adjustment are determined by emotional intelligence, meanwhile the other 67,7% are determined by other variables which are not analyzed in this study. Keywords : Emotional Intelligence, Marital Adjustment, Early Adulthood Men